Spirituality and Holistic Spiritual Health: Expanding Chaplaincy’s Theoretical Frame. By Simon Lasair. Routledge, 2025. 232 pp. $31.99 paperback - Boutros, Helana Marie (Pastoral psychology, 2026)
Simon Lasair’s Spirituality and Holistic Spiritual Health advances our understanding of what spiritual care and holistic spiritual health might entail within an increasingly secular and post-secular landscape. Though writing primarily for spiritual care practitioners, Lasair re-envisions and theoretically instantiates spiritual care for a broader readership, critically working to legitimize the field while elucidating spirituality in ways that render it both intelligible and operational within clinical practice.